Description of Biofilm Density on Glass Ionomer Cement Modified by 5% Hydroxyapatite from the Synthesis of Chicken Eggshells - Saputri, Dewi; A. Gani, Basri; Handysha, Meiditya (Faculty of Dental Medicine Universitas Airlangga, 2023)
Background: Oral microbiome biofilms can appear on all surfaces of the oral cavity as well as restorative materials such as Glass Ionomer Cement (GIC). GIC is considered superior because it has the ability to produce fluoride, which has a cariostatic effect, but the fluoride produced is inadequate to inhibit the growth of biofilms, so modifications were made by adding hydroxyapatite from eggshell. Purpose: To evaluate the levels of hydroxyapatite contained in chicken eggshells and to assess the description of oral microbiome biofilm density on the surface of hydroxyapatite-modified GIC from chicken eggshell synthesis. Methods: The research group was divided into a control group, namely GIC without the addition of hydroxyapatite, and a treatment group, namely GIC with the addition of 5% hydroxyapatite. The oral microbiome biofilm obtained from the voluntary dental plaque swab was cultured on the specimen surface at a time span of 24 hours, 48 hours, and 72 hours. Biofilm density was examined using Scanning Electron Microscopy and analyzed using ImageJ software. Results: The average density of biofilm on GIC without the addition of hydroxyapatite at 24 hours, 48 hours, and 72 hours, respectively, was 2,640.02 p/Î¼m, 1,130.08 p/Î¼m, 16,797.33 p/Î¼m. Meanwhile, the GIC with the addition of hydroxyapatite was 1,921.52 p/Î¼m, 1.029 p/Î¼m, and 5,764.50 p/m. Conclusion: Statistical analysis performed showed that time affected the density value of the oral microbiome formed, and the two groups of materials had different effects in reducing biofilm density descriptively but statistically did not have a significant difference.